HUBUNGAN KECEPATAN DDENGAN HASIL LOMPAT JAUHGAYA JONGKOK PADA SISWA KELAS V SDN 001 TERARAK KECAMATAN RUMBIO JAYA - ', Ermiati; ', Saripin; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s of male student in class V of SDN 001 Teratak Rumbio Jaya District, research found while student do run start was not optimal. The purpose of this research is to see the correlation betweeen long jump result with squat style of student in class V of SDn 001 Teratak. Population in this research used male students in class V of SDN 001 Teratak amount 50 people, 22 male students and 28 female students. Based on population that is so large the researchers set the partially of population is used as a sample. The research sample as many as 15 people. Research instrument used speed and long jump test. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : for X variable and Y variable which shows, rhitung 0,296<rtabel 0,433 Shows that there is no correlation of espeed with the result of long jump with squat style of male students in class V of SDN 001 Teratak Rumbio Jaya district. for X variable and Y variable which shows, rhitung 0,524<rtabel 0,381 Shows that there is correlation of espeed with the result of long jump with squat style of female student in class V of SDN 001 Teratak Rumbio Jaya District.Key word : speed, long jump, squat style